Effect of pembrolizumab on CD4+CD25+, CD4+LAP+ and CD4+TIM‐3+ T cell subsets. (17th February 2019) - Toor, S. M.; Sasidharan Nair, V.; Pfister, G.; Elkord, E.
Summary: Tumor immune evasion involves the expansion of avidly proliferating immunosuppressive cells and inhibition of effector T cell proliferation. Immune checkpoints (IC) block the activation pathways of tumor‐reactive T cells. IC pathways are often exploited by tumor cells to evade immune destruction, and blocking these pathways through IC inhibitors (ICI) has shown promising results in multiple malignancies. In this study, we investigated the effects of an ICI, pembrolizumab, on various T cell subsets in vitro . We compared the suppressive activity of CD4 + CD25 + regulatory T cells (conventional Treg ) with T cells expressing T cell immunoglobulin‐3 + (TIM‐3 + ) and latency‐associated peptide (LAP) + T cells. We found that LAP‐expressing T cells were more suppressive than conventional Treg, but TIM‐3‐expressing T cells were not suppressive. Our results show that pembrolizumab does not modulate functions of Treg and mediates its immunostimulatory effects via the release of effector T cells from suppression. These findings may assist in the development of agents designed to intervene in IC pathways to overcome Treg resistance to ICI. Abstract : Pembrolizumab blocks interactions between PD‐1 and ligands PD‐L1/L2 to achieve potent and prolonged immune cell responses to eliminate tumor cells. In this study, we investigated the effects of pembrolizumab on the suppressive potential of T cell subsets. Our results show that pembrolizumab does not modulate functions of Treg and mediates its immunostimulatory effects through the release of effector T cells from suppression.